The TREAT Asia HIV observational database - baseline and retrospective data - Zhou, J.; Kumarasamy, N.; Ditangco, R.; Kamarulzaman, Adeeba; Lee, C.K.C.; Li, P.C.K.; Paton, N.I.; Phanuphak, P.; Pujari, S.; Vibhagool, A.; Wong, W.W.; Zhang, F.; et al. (Lippincott, Williams & Wilkins, 2005)
Background: Relatively little is known regarding HIV disease natural history and response to antiretroviral treatments among Asian people infected with HIV The Therapeutics Research, Education, and AIDS Training in Asia (TREAT Asia) HIV Observational Database (TAHOD) is a recently established collaborative observational cohort study that aims to assess HIV disease natural history in treated and untreated patients in the Asia-Pacific region. Methods: Observational data are collected on HIV-infected patients from 11 sites in the Asia-Pacific region. Data are centrally aggregated for analyses, with the first baseline and retrospective data transferred in September 2003. Retrospective data were analyzed to assess the response to highly active antiretroviral treatment (HAART) over a 6-month period in terms of changes in CD4 count and proportions of patients achieving an undetectable HIV viral load (<400 copies/mL). Results: By the end of May 2004, 1887 patients had been recruited to the TAHOD. Seventy-two percent of patients were male, with median age 36 years. Seventy-eight percent of patients reported HIV infection through heterosexual contact. Forty-three percent of patients had a previous AIDS diagnosis, of whom 55 had tuberculosis. The mean 6-month CD4 count increase was 115 cells/muL (SD = 127) after starting triple-combination therapy. Smaller CD4 count increases were associated with a higher CD4 count before starting treatment, prior treatment with monotherapy or double therapy, and treatment with a HAART regimen containing a nucleoside reverse transcriptase inhibitor (NRTI) and/or protease inhibitor (PI) but without a non-nucleoside reverse transcriptase inhibitor (NNRTI). Five hundred and ninety-eight patients started HAART and had a viral load assessment at 6 months, with 69 attaining an undetectable viral load. Older patients, patients not exposed to HIV through heterosexual contact, and patients treated with HAART containing NRTIs and NNRTIs but without PIs were found to be more likely to achieve an undetectable level. Conclusion: Analyses of retrospective data in the TAHOD suggest that the overall response to HAART in Asian populations is similar to that seen in Western countries.